Indiscpline Cases on Learner's Academic Performance in Kashongi Sub-County, Kiruhura District. - Nimusiima, Yonab (Kabale University, 2023)
the aim of the study was to assess the relationship between indiscipline cases on learners' academic performance among primary schools in Kashongi sub county. The research study was guided by the following objectives; to analyze the causes of indiscipline cases in primary schools in Kashongi sub county, to assess the relationship between performance among primary schools in Kashongi sub-county, to find out the Possible strategies for improving discipline in schools among primary schools in Kashongi sub-county. The research was conducted using a survey research design. Both qualitative and quantitative data was used in order to enable the researcher to obtain necessary data on variables under study. Questionnaires was also used on respondents, and interviews together with focus groups applied. The findings reveal that among the challenges facing teachers in dealing with pupils' indiscipline were; inadequate support from parents and other stakeholders, ineffective guidance and counseling, withdrawal of corporal punishment, large number of pupils in a classroom, and that most schools are preoccupied with improving the mean scores. The teachers also indicated that they feared of being taken to court and interdiction by their employer.The recommendations are: